Keloids coexisting with vitiligo − A rare case series - Rayna T Velurethu; Murugesh B Shamanur; Viswanath K Belluli (Wolters Kluwer Medknow Publications, 2019)
Background Hypertrophic scars and keloid scars are a result of abnormal wound healing, in which the key feature is the excess collagen fiber secretion by fibroblasts that have been stimulated by α-melanocyte-stimulating hormone, produced by the melanocytes. Vitiligo is a common depigmenting skin disorder characterized by a total absence of the melanocytes microscopically. The observation that keloids do not occur in albinous or vitiligo patches has consolidated the theory that the melanocytes are linked to the proliferation of fibroblasts, which are central to the development of keloids. To the best of our knowledge, there is only one previous report of keloids arising over vitiligo patch. Case Series We observed three patients with keloids arising from a pre-existing vitiligo patch. All keloids were preceded by trauma. Two out of the three patients showed leucotrichia in the patch where keloid had developed. In two of our patients, we observed both a reduction in the size of the keloids as well as the repigmentation of the patches at a shorter span of time on using 5-fluorouracil as a treatment modality. Discussion According to a few studies, the number and activity of the melanocytes in the skin can be postulated to play a dominant role in pathological scar formation. However, we found three patients in whom keloids had developed on vitiligo patches. This suggests that fibroblast proliferation in keloids may not be completely dependent on just stimulation by αMSH secreted by the melanocytes, and that several other pathways may be at play to stimulate the FGF and TGF factors, which are considered central to the development of keloid.